Social inclusion of women in development and rural poverty reduction in Southern Senatorial District, Cross River State, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The study examined social inclusion of women in development and rural poverty reduction in Southern Senatorial District, Cross River State, Nigeria. The specific focus of the study was on the domains of engagement in entrepreneurship, food production involvement and cooperative society involvement. The study was built on women’s equality and empowerment model and endogenous development model. The research design adopted was survey. Data for testing the hypotheses were generated from using questionnaire and Focus Group Discussion (FGD). The sample for the study was made up of 600 respondents selected using the Cochran sample determinant. The generated data were statistically tested using Pearson Moment Correlation Coefficient and Chi-square. The tested hypotheses revealed that: engagement in entrepreneurship, food production involvement and cooperative society involvement relate significantly with rural poverty reduction. It was concluded that social inclusion of women in development activities have moderating impact of rural poverty reduction. Since rural women have made immense contribution in food security at subsistence level, more resources should be invested by government in its rural development programme to supplement the efforts of these women in food production.
Keywords: Social inclusion; women; development and rural poverty reduction